Distribution and Medical Significance of Betula Utilis in Nepal - Khatiwada, Kabita; Koirala, Sunita (International Research Journal of MMC, 2025)
This review article explores the distribution and medical significance of Betula utilis (Himalayan Silver birch) in Nepal. Across the Himalayan range, Betula utilis is found at elevations ranging from 2700 to 4500 meters. It is an important ecological component of alpine and subalpine habitats, stabilising soil and promoting biodiversity. The species is highly valued in culture and has long been used medicinally, treating infections, skin conditions, and diuretics. Its existence is, however, severely hampered by factors like habitat deterioration, overharvesting, and climate change. This review grants the investigation of the botanical description, distribution, and medicinal values of B. utilis, with emphasis on its therapeutic potential. Recognizing the plant's medicinal uses which have been in practice since years in Nepalese community could benefit drug development and conservation strategies in the Himalayan ecosystem. This review tends to focus on the miscellaneous applications of B. utilis and its possible contributions to health and leads for practices of its conservation. This paper summarizes what is now known about its pharmaceutical potential, ecological significance, distribution, and botanical individualities. It highlights the need for sustainable conservation strategies and further research to preserve this valuable species, ensuring its continued contribution to both environmental health and traditional medicine.